2023
DOI: 10.1002/smtd.202300754
|View full text |Cite
|
Sign up to set email alerts
|

Si‐Based High‐Entropy Anode for Lithium‐Ion Batteries

Xincheng Lei,
Yingying Wang,
Jiayi Wang
et al.

Abstract: Up to now, only a small portion of Si has been utilized in the anode for commercial lithium‐ion batteries (LIBs) despite its high energy density. The main challenge of using micron‐sized Si anode is the particle crack and pulverization due to the volume expansion during cycling. This work proposes a type of Si‐based high‐entropy alloy (HEA) materials with high structural stability for the LIB anode. Micron‐sized HEA‐Si anode can deliver a capacity of 971 mAhg−1 and retains 93.5% of its capacity after 100 cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…Recent studies have exploited the high entropy effect of HEAs for use in various mechanical, 49–51 catalytic, 52–54 and even biomedical applications. 55–57 Lei et al 58 for example used the high entropy effect of Si-based high entropy anode materials synthesized via ball milling and found that the material performed well as an anode for lithium-ion batteries which was able to undergo reversible structural changes during cycling, leading to its overall cycling stability.…”
Section: Definition Of High Entropy Alloysmentioning
confidence: 99%
“…Recent studies have exploited the high entropy effect of HEAs for use in various mechanical, 49–51 catalytic, 52–54 and even biomedical applications. 55–57 Lei et al 58 for example used the high entropy effect of Si-based high entropy anode materials synthesized via ball milling and found that the material performed well as an anode for lithium-ion batteries which was able to undergo reversible structural changes during cycling, leading to its overall cycling stability.…”
Section: Definition Of High Entropy Alloysmentioning
confidence: 99%
“…However, there are few novel materials for the anode that can be commercialized. Theoretical calculations and experimental studies have shown that alloying-type materials capable of forming stable intermetallic compounds with lithium, , such as Si, Sn, , Sb, Bi, and Ge, are more likely to provide energy densities exceeding the currently used carbon anodes. However, the large volume change (200% ∼ 400%) during lithiation of these materials lead to mechanical fracture, loss of electrical contact, and unstable solid electrolyte interface (SEI) layers that impede reaction kinetics and reduce cycling stability. , Optimization of the size and morphology of these alloying-type materials are considered crucial to solving these problems. …”
mentioning
confidence: 99%